Pengaruh Tingkat Kemampuan Akademik Siswa SMA Kota Malang terhadap Sikap pada Ekosistem Sungai - Mochammad Iqbal; Susriyati Mahanal; Siti Zubaidah; Duran Corebima Aloysius (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2015)
The environmental conditions which are becoming worse is the potential problems facing humanity. Many efforts have been made to reduce environmental damage, one of them is by instilling environmental awareness through education. This education can be done through the application of learning that capable of empowering students positive attitude towards the environment. The reality on the field, the student academic abilities level are very diverse,necessitating a study to assess the effect of student academic level toward the changes in students attitudes through learning process. This study aims to determine the effect of the variation of academic ability on the attitudes toward river ecosystem of high school students in the city of Malang. This study conducted in academic years of 2008/2009. The subjects in this study were high school students in Malang, and the samples are SMAN 2 Malang students from class X7 and X8 and SMA Laboratorium UM students from class X2 and X6. This study applied to the second semester of 10 th grade students on the topic of River Ecosystem. The data statistical analysis from this study showed that the probability of academic ability is 0.376 (bigger than 0.05), so that thenull hypothesis is accepted and the research hypothesis is rejected, which means academic ability had no effect on student attitudes on the ecosystem of the river. Thus, it can be concluded that learning processes that aims to empower student positive attitude on the river ecosystem can be applied both to students with high and low level of academic ability Keywords: academic ability, attitude, river ecosystem